Captivating Illusions: Sexual Abuse and the Ordering of Love - Traina, Cristina L. H. (Journal of the Society of Christian Ethics, 2008)
Adults typically take pleasure in the physical dimension of caring for children. Confusingly, much recent theology either condemns adults' physical enjoyment of children as exploitive or accepts it (in maternal care of infants) without comment. A convincing, unifying theological moral argument is needed to yoke the two instincts systematically. Although this essay acknowledges sexual abuse's harmful effects on children, its focus is the ordering of adult desire and behavior. Beginning from the premise that all human love is erotic—hoping in, if not expecting, pleasurable reciprocity—I draw upon the work of Wendy Farley and Linda Holler to argue that healthy human love for children combines desires for the other with unpossessive delight, attunement, and realistic responsiveness. I examine the documented examples of female abuse of children and the example of male abuse in Vladimir Nabokov's Lolita to demonstrate the usefulness of this discussion for an analysis of Western accounts of abuse, and I suggest that the approach may be illuminating in other cultures.